Perioperative Smoking Cessation and Clinical Care Pathway for Orthopaedic Surgery. Issue 8 (August 2017) - Truntzer, Jeremy; Comer, Garet; Kendra, Matthew; Johnson, Joey; Behal, Raj; Kamal, Robin N.
Abstract : Despite efforts to curtail tobacco use, smoking continues to be the leading preventable cause of death both in the United States and internationally. Tobacco use is associated with a number of systemic complications as well as orthopaedic-related complications. New quality measures by the Centers for Medicare & Medicaid Service have placed greater emphasis on reducing smoking-related complications, which also directly impact physician reimbursement. An orthopaedic surgeon is an important member of the care team to initiate smoking cessation with a simple discussion of a patient's tobacco use and willingness to quit. Multiple clinical pathways are available that may be implemented to coordinate care among physicians, staff, and counselors.